2008
DOI: 10.1007/s00449-008-0212-x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between biofilm development, structure and detachment in rotating annular reactors

Abstract: In biotechnology, composition of biofilms and suspended bioaggregates can be crucial for system performance or product quality. Consequently, understanding biofilm dynamics is important for any process optimisation. The aim of this study was to investigate biofilm development and detachment under different hydrodynamic conditions and varying glucose load. Confocal laser scanning microscopy proved to be a fast method providing information about structure, distribution and volume ratio of bacteria and extra cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 40 publications
0
41
0
Order By: Relevance
“…Both modelling [66,67] and experimental studies [57,68] have revealed the important roles that, for example, shear-stress-induced detachment of cells or increased oxygen transport to a biofilm in turbulent flow conditions play on the structure and growth of an established biofilm. From an engineering perspective, this does give some inkling of ways of managing the flow of the water distribution system to control the sloughing of biofilm material into the bulk water that ultimately emerges at the tap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both modelling [66,67] and experimental studies [57,68] have revealed the important roles that, for example, shear-stress-induced detachment of cells or increased oxygen transport to a biofilm in turbulent flow conditions play on the structure and growth of an established biofilm. From an engineering perspective, this does give some inkling of ways of managing the flow of the water distribution system to control the sloughing of biofilm material into the bulk water that ultimately emerges at the tap.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 5 mL samples were filtered on 47 mm Whatman ® 0.2 µm membrane filters (Sigma-Aldrich, Gillingham, UK) and subsequently the surface area that biofilms from the bulk water covered on the membrane filters was determined by fluorescence microscopy using the 1000× magnification. In order to stain the cells of the biofilms, 1 mL of 10 µg/mL of DAPI was used; in order to stain the extracellular polymeric substances (EPS) of the biofilms, 1 mL of 10 µg/mL of fluorescein Aleuria aurantia lectin (Vector laboratories, Peterborough, UK) was used [57]. The composite image of biofilms was created using the Matlab command called "imfuse".…”
Section: Flow Conditionsmentioning
confidence: 99%
“…This may have been because the DO concentration was affected by the mass transfer resistance inside the biofilm. Also, more aerobic bacteria stayed near the biofilm surface, which led to a greater oxygen consumption in the aerobic reaction (Garny et al 2008;Pan et al 2016). Similarly, the DO decrease gradient was lower near the bottom of the biofilms, probably because of the facultative and anaerobic organisms located there.…”
Section: Oxygen Transfer Inside the Biofilms Under Different Aerationmentioning
confidence: 94%
“…Sloughing was defined as the loss of large parts of a biofilm. This process can be induced by rapid changes in environmental conditions such as a sudden increase in shear force (Elenter et al, 2007;Telgmann et al, 2004), sudden depletion in oxygen concentration (Thormann et al, 2005) or nutrients (Garny et al, 2008;Hunt et al, 2004). However, little is known about the causes of spontaneous sloughing events and the effect of subsequent biofilm development.…”
Section: Introductionmentioning
confidence: 99%
“…Biological factors include growth rate (Bakke et al, 1984), cell motility (O'Toole and Kolter, 1998), quorum sensing (McLean et al, 2005), extracellular enzyme production (Kaplan et al, 2004), EPS (Sutherland, 2001) and predation (Parry, 2004;Weitere et al, 2005). Chemical factors are for example, nutrient availability (Garny et al, 2008;Horn et al, 2001;Stoodley et al, 2001) and pH, while physical parameters are fluid shear (van Loosdrecht et al, 1995;Wäsche et al, 2002), temperature (Piao et al, 2006) or particle collision (Kwok et al, 1998).…”
Section: Introductionmentioning
confidence: 99%